Unusual presentation of immunoglobulin G4-related disease: A case report - Gözde ZEYBEK; Sevinç KALIN; Burcu KARAKAYALI; Ebru ZEMHERİ and Sait NADERİ and Betül SÖZERİ5 (Archives of Rheumatology, 2021)
Immunoglobulin G4-related disease (IgG4-RD) is an inflammatory disease characterized by a tumor-like infiltration of IgG4 positive plasma cells and fibrosis in various organs. The exact pathogenesis remains unknown. In this article, we discuss the diagnostic management of IgG4-RD with reference to clinical, serologic, pathological and radiological data on a 17-year-old male patient with lumbar vertebral involvement.